Bound excitons in low dimensional halide perovskites - Chong, Wee Kiang (2017)
Lasers and light emitting diodes are found in numerous applications in our daily lives. The performance and applications of these diodes are very dependent on the choice of light emitting material. Ideally, these materials should be brightly emitting, solution-processible, low cost, and tunable. Among the vast variety of light emitting materials, three dimensional organic-inorganic halide perovskites are found to inherit these characteristics. As such, their light emitting and optical gain properties have been in the limelight over the past few years. On the contrary, not much attention was given to their low dimensional counterparts, which exhibit bright excitonic emission. In these low dimensional systems, the role of bound excitons cannot be neglected as they are an important species that influences light emitting and optical gain properties. In particular, this work explores the role of bound excitons in these perovskites for optical gain and white emission, which could be attractive for electrically pumped gated laser and white LEDs respectively. Bound excitons, in particular defect-bound excitons, were found to be one of the problems in limiting low temperature biexcitonic optical gain in (C6H5C2H4NH3)2PbI4 two dimensional perovskites. In this material, biexcitonic states were found to be populated through free-to-bound excitonic relaxation followed by bound-to-biexcitonic relaxation. Through these relaxation pathways, both free and bound excitonic recombinations can take place, which effectively compete withbiexcitonic population inversion build up. Theoretical modelling revealed a high biexcitonic optical gain threshold, which is consistent with the presence of strongly competing relaxation channels. Low optical damage threshold is another problem that is inherent in this material. This threshold, which is ∼1 order of magnitude lower than the theoretical biexcitonic optical gain threshold, could impede the path to achieving optical gain. On the other hand, bound excitons, in the form of self-trapped excitons, are responsible for white emission from low dimensional perovskites, such as (C6H5C2H4NH3)2PbCl4 and (NH3CH2C6H4CH2NH3)PbBr6. Notably, white emission is only observed in the latter thin films fabricated with excess PbBr2. Importantly, these excitons were found to undergo self-trapping at different locations in the two materials, with exciton self-trapping at the organic framework for the former and at the inorganic framework for the latter. Nonetheless, large exciton-phonon coupling strength, which is indicative of self-trapped excitons, was measured from both materials. Self-trapping phenomenon at the organic framework provide a new perspective on the origin of white emission in these systems, which deviates from conventional understanding of self-trapping in inorganic semiconductor systems. These two findings suggest that judicious selection of both organic and inorganic precursors are crucial for developing high efficiency white emitting perovskites. In retrospect, the presence of bound excitons in low dimensional perovskites serves as a double-edged sword, which either limits optical gain or gives rise to white emission.